The Impact of Legislative Standards on Batterer Intervention Program Practices and Characteristics. Issue 1 (31st January 2014) - Boal, Ashley L.; Mankowski, Eric S.
Abstract: Changes in social policy are often pursued with the goal of reducing a social problem by improving prevention efforts, intervention program practices, or participant outcomes. State legislative standards for intimate partner violence intervention programs have been adopted nearly universally across the US, however, we do not know whether such standards actually achieve the intended goal of affecting programs' policies and practices. To assess the effect that batterer intervention program (BIP) standards have on policies and practices of programs, this study used longitudinal surveys collected as part of an ongoing evaluation conducted from 2001 to the present to compare intervention program ( N = 74) characteristics and practices at three time points before and after the adoption of standards in Oregon. Analyses were conducted to examine all BIPs in Oregon at each time point, as well as change among a subset of programs in existence at all survey assessments. Results indicate that across all programs, the use of mixed gender group co‐facilitation increased by 14 % between 2004 and 2008, while program length increased by approximately 12 weeks. However, other practices such as programs' coordination with community partners were unchanged. Analyses of within‐program change revealed fewer differences, with only program length increasing significantly over the three assessments. These and other findings indicate that while standards affected program length as intended, other practices commonly addressed by legislative standards remained unchanged. The findings provide needed information regarding programs' compliance with components of the standards, the potential need for compliance monitoring, and the potential impact of state standards on program effectiveness and on the prevalence of intimate partner violence.